(untitled) (Slavic Studies, 2025)
Literature plays a crucial role in teaching Polish as a foreign literature, offering rich resources for acquiring culture in an enjoyable way. The use of literary texts as didactic material in teaching Polish as a foreign language has a long-standing tradition. Literary texts provide extensive support for illustrating specific linguistic phenomena, enriching lexical and morphosyntactic structures, and stimulating conversational skills through engaging topics. This paper explores the benefits of incorporating literary texts into Polish language and culture classes, highlighting their role in developing analytical skills, expanding vocabulary, and deepening cultural understanding. The analysis focuses on Olga Tokarczuk’s novel The Books of Jacob, which offers a broad panorama of the socio- political, multiethnic, and multicultural reality of 18th-century Poland. The novel serves as an exemplary tool for illustrating various aspects of Polish culture, such as daily life, traditions, and historical events. Additionally, the contributions of figures like Benedykt Chmielowski and the Załuski brothers to Polish culture are examined, emphasizing their impact on education and the preservation of the cultural heritage. The paper concludes that well-chosen literary texts significantly enhance the learning process by fostering sociolinguistic competence and broadening students’ intellectual horizons.